2022
DOI: 10.3390/math10152569
|View full text |Cite
|
Sign up to set email alerts
|

Redesign of the Statistics Course to Improve Graduates’ Skills

Abstract: In general, college students have concerns about mastering the Statistics course. Several scientific articles suggest that methodologies in which the student is an active part of the educational process lead to their greater involvement in teaching activities and better results in their overall assessment. A modified form of the Mathematics course inspires this study. The Mathematics course precedes the Statistics course. This study presents students’ results from both affected courses for the last 12 years. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…At the same time, Benková et al [28] redesign a statistics course to improve the skills of graduates using the active learning methodology, the course was redesigned taking into account the opinions of graduates through the use of a survey, then the results of the evaluations of students enrolled in virtual modality that use the previous methodology and students that use the new methodology, it was identified that with the application of the active learning methodology the students significantly improved their learning, developed soft skills and a better understanding of statistical methods.…”
Section: B Clustering and Thematic Analysismentioning
confidence: 90%
See 1 more Smart Citation
“…At the same time, Benková et al [28] redesign a statistics course to improve the skills of graduates using the active learning methodology, the course was redesigned taking into account the opinions of graduates through the use of a survey, then the results of the evaluations of students enrolled in virtual modality that use the previous methodology and students that use the new methodology, it was identified that with the application of the active learning methodology the students significantly improved their learning, developed soft skills and a better understanding of statistical methods.…”
Section: B Clustering and Thematic Analysismentioning
confidence: 90%
“…Twenty-six articles examined the impact of materials-based teaching, with the studies exploring various materials employed for teaching statistics to assess their effect on the advancement of statistical literacy. These materials encompassed the development of applications using statistical software [53][54][55][56][57][58][59][60], virtual simulators [25,29,30,36,61,62], real-time data analysis [19,20,25,28,33], interactive applications [63][64][65], and internet pages [31,32,34].…”
Section: Material-focused Teaching Methodsmentioning
confidence: 99%
“…The notion of active learning in higher education can be traced back to the 1980s (Pan & Fan, 2020). Active learning is a teaching approach that involves students to actively participate in the learning process (Benková et al, 2022;Prince, 2004). Active learning can be geared toward case-based, collaborative, cooperative, problem-based, and team-based learning (Collins & McLain, 2021;Prince, 2004).…”
Section: Active Learningmentioning
confidence: 99%
“…Active learning advance students to inquire, experiment, collaborate, and experience the joy of learning (Budihal et al, 2020). To engage in active learning, students must engage in higher-order thinking tasks, including analysis, evaluation, and synthesis, to solve problems (Benková et al, 2022). Thus, active learning can support and develop critical skills, such as communication, cooperation, creativity, critical thinking, and knowledge-gathering (Benková et al, 2022).…”
Section: Active Learningmentioning
confidence: 99%
See 1 more Smart Citation